2022
DOI: 10.3390/cancers14225711
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in Epithelial Ovarian Cancer: From Biomarkers to Therapeutic Targets

Abstract: Epithelial ovarian cancer (EOC) is the most lethal gynecological cancer, and more than 70% of patients are diagnosed at advanced stages. Despite the application of surgery and chemotherapy, the prognosis remains poor due to the high relapse rate. It is urgent to identify novel biomarkers and develop novel therapeutic strategies for EOC. Circular RNAs (circRNAs) are a class of noncoding RNAs generated from the “back-splicing” of precursor mRNA. CircRNAs exert their functions via several mechanisms, including ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 219 publications
0
5
0
Order By: Relevance
“…Thus, circRNAs are characteristically stable and have longer half-lives than their precursor mRNAs and other noncoding RNAs (microRNAs and long noncoding RNAs). Some glycolysis-associated circRNAs, which are abnormally expressed in the plasma exosomes of patients with GI cancers, have the potential to be used as liquid biopsy biomarkers for early detection of GI cancers [ 100 ]. For example, circPDK1 is significantly upregulated in the plasma exosomes and tumor tissues of patients with PC and promotes cell proliferation and glycolysis in vitro and in vivo.…”
Section: Clinical Significance Of Glycolysis-associated Circrnas In G...mentioning
confidence: 99%
“…Thus, circRNAs are characteristically stable and have longer half-lives than their precursor mRNAs and other noncoding RNAs (microRNAs and long noncoding RNAs). Some glycolysis-associated circRNAs, which are abnormally expressed in the plasma exosomes of patients with GI cancers, have the potential to be used as liquid biopsy biomarkers for early detection of GI cancers [ 100 ]. For example, circPDK1 is significantly upregulated in the plasma exosomes and tumor tissues of patients with PC and promotes cell proliferation and glycolysis in vitro and in vivo.…”
Section: Clinical Significance Of Glycolysis-associated Circrnas In G...mentioning
confidence: 99%
“…Evidence has suggested that circRNAs could play an oncogenic role or exert tumor suppressive functions in ovarian cancer ( Zhang et al, 2022a ; Ghafouri-Fard et al, 2022 ; Najafi, 2023 ). Moreover, circRNAs might be biomarkers for diagnosis and prognosis in ovarian cancer ( Qiu et al, 2022 ). For instance, circRNA1656 was reported to act as a potential biomarker in high grade serous ovarian cancer ( Gao et al, 2019a ).…”
Section: Drug Resistancementioning
confidence: 99%
“…miR-449b-5p is recognized as a tumor suppressor that regulates tumor proliferation, metastasis, and invasion ( Garber, 2004 ; Chen et al, 2020 ; Huang et al, 2020 ). CHD1, a regulator in maintaining genome stability, promotes DNA transcription by keeping DNA in an open and transcriptionally active state through ATP-dependent assembly, transfer, and removal of nucleosomes from DNA ( Li et al, 2020 ; Qiu et al, 2022 ). It has been emphasized that CHD1 degradation suppresses glioma cell proliferation and glycolysis ( Jeck et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%